Metodologias de ensino: um estudo da prática docente em música durante a pandemia COVID-19 - ARAÚJO, Flávio Lopes de (2024)
This dissertation — which investigates the teaching activity developed by music teach ers at Instituto Federal do Piauí (IFPI), Teresina Central Campus, during the period of the Covid-19 pandemic (2020-2021) — aims to identify the methodological solutions, as well as the learning strategies implemented by music educators working on the Technical Musical Instrument Teaching Course at the IFPI, Teresina Central Campus, in the face of the challenges imposed by social isolation. In the methodological path way, we conducted a descriptive-exploratory study using a qualitative approach. The data collection instrument used was an online questionnaire applied to nine music teachers who taught remote classes during the coronavirus pandemic. To analyze the data collected, we chose content analysis (Bardin, 1987) as an investigative method. At the end of the study, it was demonstrated not only that mastery of information and communication technologies was decisive for the quality of teaching for the new teach ing modality that was now emerging, but also that planning and investment are needed for the organized construction of teaching in its remote form. The results support the continued construction of new knowledge focused on technology and the digital world. We hope that these results, aligned with the other knowledge, will provoke a concep tual change in teachers and managers regarding teaching methodologies.